Association of perinatal characteristics with biomarkers of stress and inflammation in young adults: An exploratory study - Plank, Anne-Christine; Maschke, Janina; Mestermann, Stefan; Janson-Schmitt, Johanna; Sturmbauer, Sarah; Eichler, Anna; Rohleder, Nicolas (Comprehensive Psychoneuroendocrinology, 2024)
General peri- and postnatal characteristics may serve as markers linking pre- or early postnatal events to later health outcomes, which in turn are associated with altered stress- and immune system activity. Our exploratory study investigated whether A) the common perinatal measures “birth weight” and “birth mode” and B) the postnatal characteristics “breastfeeding” and “vaccination status” are associated with markers of stress systems – the hypothalamic-pituitary-adrenal (HPA) axis and autonomous nervous system (ANS) – and inflammation in healthy young adults (n = 68, females: 70.6 %, mean age: 24.21 years, SD = 4.38) exposed to psychosocial challenge, the ‘Trier Social Stress Test’ (TSST). Salivary cortisol, alpha-amylase (sAA) and plasma interleukin-6 (IL-6) were assessed before, during and after the TSST. Participants provided information on peri- and postnatal characteristics. Linear regressions were performed to determine whether peri-/postnatal variables predict basal and stress-response-related biomarker levels. Controlling for sex and sex hormone use as relevant confounders, we found a significant association between birth weight and cortisol recovery (p = 0.032), with higher birth weight predicting higher cortisol recovery values. There were no other significant associations between predictor and outcome variables. Our results show that, in healthy young adults of mixed gender, normal-ranged birth weight is related to the cortisol response to psychosocial stress, indicating a long-term association of this perinatal marker with HPA axis function. In contrast, birth weight was not associated with markers of the ANS stress response or inflammation in adulthood. Our results further suggest that the measures birth mode, duration of breastfeeding, and vaccination status at 4 months of age do not relate to markers of the inflammatory and stress systems in adulthood.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Alpha-amylase; Birth weight; Cortisol; IL-6; Perinatal markers; Stress response